European integration as a threat to social security: Another source of Euroscepticism?. (June 2018) - Baute, Sharon; Meuleman, Bart; Abts, Koen; Swyngedouw, Marc
This study investigates whether citizens' concerns about the EU's impact on social security are a distinct source of Euroscepticism. By analysing data from the European Values Study 2008, we show that citizens differentiate between domain-specific fears about European integration (i.e. about social security, national sovereignty, culture, payments and jobs), meaning that they cannot be reduced completely to a general fear about European integration. Furthermore, socioeconomic determinants and ideological position are more important in explaining citizens' fear about the EU's impact on social security than in explaining their generalised fear of European integration. In countries with higher social spending, citizens are more fearful of European integration in general, however, social spending does not affect fears about social security more strongly than it affects other EU-related fears.